PEMBUATAN VIDEO PROFIL MENGGUNAKAN FLAT ANIMATION SEBAGAI MEDIA PROMOSI PADA DEVELOPER APLIKASI PROTOKOL - Ismail Abdurrozzaq Zulkarnain (SPEED - Sentra Penelitian Engineering dan Edukasi, 2019)
Abstract - This study aims to create profile videos using flat animation as a promotional tool for Protocol application developers. The method used in making this promotional media is the Animation Make method. Animation with this technique has a sprite that is continuously generated by the program, then displayed with certain calculations. While the method used in this study is Action Research. Methods of data collection by means of observation, interviews and questionnaires involving 8 expert respondents and 6 prospective customer respondents. Data analysis using qualitative descriptive analysis. This study includes 3 stages. Stage 1 is pre-production which includes concepts, scenarios, character building, storyboarding, music and FX sound. Stage 2 is the production stage which includes layouts, key motion, in between, clean up, background, celluloid, coloring. Stage 3 is the post-production stage which includes composite, camera shooting, editing, rendering. The results of this study indicate that the type of Flat Animation can make promotional media in the form of video profiles become more attractive and objective in the delivery of information. Keyword : Video Profile, Promotion Media, Flat Animation